2015
DOI: 10.1017/s0031182015001572
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune response in intraventricular experimental neurocysticercosis

Abstract: Neurocysticercosis (NCC) is considered a neglected parasitic infection of the human central nervous system. Its pathogenesis is due to the host immune response, stage of evolution and location of the parasite. The aim of this study was to evaluate the in situ and systemic immune response through cytokines dosage (IL-4, IL-10, IL-17 and IFN-γ) as well as the local inflammatory response of the experimental NCC with Taenia crassiceps. The in situ and systemic cellular and inflammatory immune response were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
(101 reference statements)
1
17
0
Order By: Relevance
“…All the control animals showed discrete levels of edema and hyperemia due to the mechanical trauma of the inoculation of sterile saline solution. These discrete alterations in the control group have also been observed in other experimental NCC studies 6,13,18,21 . In the infected animals, the majority of the cysticerci were located inside the lateral ventricles accompanied by a discrete-to-moderate intensity of inflammatory response.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…All the control animals showed discrete levels of edema and hyperemia due to the mechanical trauma of the inoculation of sterile saline solution. These discrete alterations in the control group have also been observed in other experimental NCC studies 6,13,18,21 . In the infected animals, the majority of the cysticerci were located inside the lateral ventricles accompanied by a discrete-to-moderate intensity of inflammatory response.…”
Section: Discussionsupporting
confidence: 82%
“…Matos-Silva et al 6 also found similar results using the T. crassiceps NCC model. Using the same model, Moura et al 18 described a predominance of the Th2 immune profile cytokines at the end of the infection, while in the acute phase of the infection there was a mixed Th1/Th17 profile accompanied by high levels of IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are directly injected in the peritoneal or intracranial cavity, which is not their natural route of infection. Moura et al., (2015) used the same model to study the cellular immune response. They noticed mixed Th1/Th17 responses at acute phase of infection and a predominantly Th2 response at late stage.…”
Section: Animal Models For Neurocysticercosismentioning
confidence: 99%
“…The immune response in mice infected with T. crassiceps is not well described in NCC models. However, Moura et al 15 , studying an intraventricular experimental NCC model, reported that BALB/c mice presented with a predominance of a systemic mixed Th1/Th17 immune profile in the initial phases of the infection, while this gradually modified into a Th2 profile through the course of the infection.…”
mentioning
confidence: 99%